Effect of Percutaneous Coronary Intervention (PCI) on Quality of Life in Patients with Stable Coronary Disease - Shahzad, Trique Ahmed, Nasir Ali, Muhammad Asim Shaikh, Aslam Latif Bhutto, Abdul Mueed, Jawaid Akbar Sial, Natasha Niaz, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The most popular form of treatment for coronary disease is percutaneous coronary intervention (PCI). Along with recurrence rates and mortality, quality of life (QoL) is a crucial PCI outcome indicator. Purpose: The purpose of this research was to look at the variables affecting individuals with coronary disease who had undergone PCI's quality of life. The cardiac center of the hospital provided a convenient sampling for this descriptive, cross-sectional research. On a population of 630 patients who had coronary disease, this research was carried out utilizing a standardized questionnaire and individual medical data. Information on general, medical, and psychological traits was gathered using the questionnaire. Descriptive statistics, the independent t-test, one-way variance analysis and Scheffé test were all used to analyze the data. The significant variables in univariate analysis were combined with the key parameters found in a multiple linear regression to identify the factors that strongly affected QoL. Results: We discovered that age, subjective economic status, being the primary caregiver, time since the first PCI, anxiety, and depression all significantly influenced QoL. The Age, primary caregivers and marital status were the strongly significant variables that were proven to have an impact on QoL in patients who had gone through PCI. The period since the initial PCI was among the main clinical factors that were proven to have an impact on QoL. Depression and anxiety were among the important psychosocial traits that were found to have an impact on quality of life. The study's PCI patients' primary caregivers were shown to have the biggest influence on their quality of life. Conclusions: Patients' post-PCI psychological and physical symptoms must be frequently evaluated in order to improve QoL in those who had underwent PCI. In addition, patients with significant functional impairments and those getting family care need intervention measures that aim at enhancing quality of life.